Differential activation of amygdala Arc expression by positive and negatively valenced emotional learning conditions - Young, Erica; Williams, Cedric L. (Frontiers in Behavioral Neuroscience, 2013)
Norepinephrine is released in the amygdala following negatively arousing learning conditions. This event initiates a cascade of changes including the transcription of activity-regulated cytoskeleton-associated protein (Arc) expression, an early-immediate gene associated with memory encoding. Recent evidence suggests that the valence of emotionally laden encounters may generate lateralized, as opposed to symmetric release of this transmitter in the right or left amygdala. It is currently not clear if valence-induced patterns of selective norepinephrine output across hemispheres are also reproduced in downstream pathways of cellular signaling necessary for memory formation. This question was addressed by determining if Arc expression is differentially distributed across the right and left amygdala following exposure to positively or negatively valenced learning conditions respectively. Male Sprague Dawley rats were randomly assigned to groups exposed to the Homecage only, five auditory tones only, or five auditory tones paired with footshock (0.35 mA) during Pavlovian fear conditioning. Western blot analysis revealed that Arc expression in the right amygdala was elevated significantly above that observed in the left amygdala 60 and 90 min following fear conditioning. Similarly, subjects exposed to a negatively valenced outcome consisting of an unexpected reduction in food rewards showed a greater level of Arc expression in only the right, but not left basolateral amygdala. Presenting a positively valenced event involving an unexpected increase in food reward magnitude following bar pressing, resulted in significantly greater Arc expression in the left, but not right basolateral amygdala (p < 0.01). These findings indicate that the valence of emotionally arousing learning conditions is reflected at later stages of synaptic plasticity involving the transcription of immediate early genes such as Arc.